TRANSLATING THE ENGLISH PREPOSITION “OF” INTO INDONESIAN - Huda, Khoirul (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This paper is an attempt to seek solution to the problem of translating the source language containing the English preposition “the” into well-accepted form in Indonesian as the target language. Some equivalent alternatives such as dari, tentang, sebagai, terhadap, untuk, dari antara, -nya and its zero equivalent signified as ø are discussed. The Analysis of the samples of the data taken from Newton’s “Twentieth Century Literary theory” indicates that the equivalent words such as “dari” and “ø” have appeared as the first and second most frequent equivalents.